Respuesta :

Answer:

m = -18

Step-by-step explanation:

6 + m/2 = -3

Subtract 6 from each side

6 + m/2 -6 = -3-6

m/2 = -9

Multiply each side by 2

m/2 * 2 = -9*2

m = -18

[tex]\huge\text{Hey there!}[/tex]

[tex]\huge\boxed{\mathsf{6+ \dfrac{m}{2}=-3}}}\\\huge\boxed{\rightarrow\mathsf{6 + \dfrac{1}{2}m = -3}}[/tex]

[tex]\huge\boxed{\rightarrow \mathsf{\dfrac{1}{2}m+ 6 = -3}}\\\\\huge\boxed{\text{SUBTRACT 6 to BOTH SIDES}}\\\huge\boxed{\mathsf{\dfrac{1}{2}m + 6 - 6 = -3 + 3}}[/tex]

[tex]\huge\boxed{\mathsf{\dfrac{1}{2}m = -9}}[/tex]

[tex]\huge\boxed{\text{MULTIPLY 2 to BOTH SIDES}}[/tex]

[tex]\huge\boxed{\mathsf{\dfrac{1}{2}m \times 2 = 2 \times -9}}[/tex]

[tex]\huge\boxed{\mathsf{m = 2\times-9}}\\\huge\boxed{\mathsf{2\times-9 = m}}\\\huge\boxed{\mathsf{2\times-9 = \bf -18}}\\\\\huge\boxed{\textsf{Therefore, your answer: \bf -18}}\huge\checkmark[/tex]

[tex]\huge\text{Good luck on your assignment \& enjoy your day!}[/tex]

~[tex]\huge\boxed{\frak{Amphitrite1040:)}}[/tex]